Correlation between hydration status and VO2max in Pencak Silat athletes - Fadilah Umar; Nabela Dea Sari; Slamet Widodo; Ann Mahakeeta; M Misbah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Maintaining proper hydration conditions is important to support athlete performance. The study aimed to determine the relationship between hydration status and the VO2max capacity of martial arts athletes. The research was conducted using a correlational method. The subjects of the study were 14 Pencak Silat Athletes Special Class for Sports at State Junior High School (JHS) 1 Surakarta. Self-Urine Check (SUC) test data collection to test hydration status and Bleep Test to measure athletes' VO2max capacity. Data analysis techniques with product-moment correlation tests. The results obtained the relationship coefficient between hydration status and VO2max capacity was r = -0.844; p = 0.001. Therefore, there was a significant negative relationship between these two variables. This study concludes that there was a negative correlation between hydration status and VO2max capacity in JHS Special Sports Class athletes. The novelty of this study lies in the observation of stable hydration levels among Pencak Silat athletes in the Special Sports Class of SMPN 1 Surakarta. The results of this study can be used as a reference for athletes to maintain adequate hydration during activities, and for coaches to ensure that all athletes are in a well-hydrated state to avoid dehydration.